2012
DOI: 10.1007/s13758-012-0042-x
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of the Cyclic Wetting Mechanism in the Active Part of Wheat Awns

Abstract: Many plant tissues and organs are capable of moving due to changes in the humidity of the environment, such as the opening of the seed capsule of the ice plant and the opening of the pine cone. These are fascinating examples for the materials engineer, as these tissues are non-living and move solely through the differential swelling of anisotropic tissues and in principle may serve as examples for the bio-inspired design of artificial actuators. In this paper, we model the microstructure of the wild wheat awn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This whole subject of hydrogels that respond to external stimuli is an area of research in its own right, and the readers are referred to further reviews. 150 Returning to the natural systems that display changes in shape upon actuation in water, a finite element modeling study by Zickler et al 151 showed that the probable mechanism for the swelling and shape changes in wheat awns is the formation of gaps between laminations, which act as valves, allowing moisture into the cell walls. This interplay of structure of laminations, and the molecular level of cellulose and its interactions with water demonstrate that there are most likely hierarchical features that lead to macroscopic behavior.…”
Section: Hygromorphic Responsive Cellulose-based Composite Hydrogelsmentioning
confidence: 99%
“…This whole subject of hydrogels that respond to external stimuli is an area of research in its own right, and the readers are referred to further reviews. 150 Returning to the natural systems that display changes in shape upon actuation in water, a finite element modeling study by Zickler et al 151 showed that the probable mechanism for the swelling and shape changes in wheat awns is the formation of gaps between laminations, which act as valves, allowing moisture into the cell walls. This interplay of structure of laminations, and the molecular level of cellulose and its interactions with water demonstrate that there are most likely hierarchical features that lead to macroscopic behavior.…”
Section: Hygromorphic Responsive Cellulose-based Composite Hydrogelsmentioning
confidence: 99%
“…Sorption-induced pressures or deformations are of obvious interest for applications of nanoporous media as sensors or mechanical actuators. In the case of soft porous materials, e.g., aerogels [175], porous polymers [176] and biomaterials [156], the deformations are particularly large and can therefore be used for large-scale, reversible locomotion [177,178,179] induced via fluid sorption. And this in a remarkably energyefficient manner, as has been documented in a recent study on water sorption-induced deformation of wood by Bertinetti, Fischer and Fratzl [180].…”
Section: Sorption-induced Matrix Deformation Young-laplace and Tensil...mentioning
confidence: 99%
“…self-opening windows) [9,64]. In terms of implementation, computational models would help decipher the interaction between morphological and compositional gradients, and how these features could be an asset for the design of synthetic systems [6567]. This would be a starting point for the realization of proof-of-concept prototypes for novel multi-objective, programmable origami composites and metamaterials with uses in a variety of applications [11,6870].…”
Section: Discussionmentioning
confidence: 99%
“…self-opening windows) [9,64]. In terms of implementation, computational models would help decipher the interaction between morphological and compositional gradients, and how these features could be an asset for the design of synthetic systems [65][66][67].…”
Section: Comparison Of Functionally Graded Material-based Deformation In S Lepidophylla To Other Established Plant Modelsmentioning
confidence: 99%